The 100 Most Influential Musicians of All Time - Edited by Gorlinski, Gini (New York Britannica Educational Pub., 2010)
Chronologically arranged entries profile one hundred of the world's most influential musicians from medieval times through the twentieth century.
Includes Glossary, Illustrations and index.
Keywords: Musicians -- Biography